ASSESSING CYCLE LANES USING THE BICYCLE COMPATIBILITY INDEX (BCI) IN SHAH ALAM, SELANGOR, MALAYSIA - Abdullah, Yusfida Ayu; Ahmad Razi, Syifa’Azwa; Nasrudin, Na’asah; Ahmad Zaki, Zulkifli (PLANNING MALAYSIA, 2020)
The evolution of bicycles is tremendous. Humans recognized its function, importance, and value this non-motorized vehicle as an important part of their daily life. In Malaysia, most urban roads are designed for the motor vehicle therefore cycling is not a greater option for commuting to workplaces. This study aims at assessing the compatibility level of cycle lanes. Section 14, Shah Alam, Malaysia was selected as the case study, and a questionnaire survey utilizing the Simple Random Sampling technique was conducted involving 133 samples. The Bicycle Compatibility Index (BCI) was applied to calculate the capability of bicycle lanes. Results demonstrated the weaknesses of bike path infrastructure and its compliance to guidelines. The compatibility level of cycle lanes is still low, therefore, suggesting an enhanced approach to the planning and development of cycle lanes. The outcome of this study can be a guide to the local authority yet applicable to other urban areas.